The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1126/scitranslmed.aai7459
|View full text |Cite
|
Sign up to set email alerts
|

mGlu 7 potentiation rescues cognitive, social, and respiratory phenotypes in a mouse model of Rett syndrome

Abstract: Rett syndrome (RTT) is a neurodevelopmental disorder caused by mutations in the methyl-CpG binding protein 2 (MECP2) gene. The cognitive impairments seen in mouse models of RTT correlate with deficits in long-term potentiation (LTP) at Schaffer collateral (SC)–CA1 synapses in the hippocampus. Metabotropic glutamate receptor 7 (mGlu7) is the predominant mGlu receptor expressed presynaptically at SC-CA1 synapses in adult mice, and its activation on GABAergic interneurons is necessary for induction of LTP. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 53 publications
3
78
1
1
Order By: Relevance
“…Motor Cortex and Cerebellum RNA Sequencing. We recently obtained six cerebellum samples from RTT patient autopsies to serve as a complement to our existing work in the motor cortex, as well as eight age, sex, and PMI matched controls [described further in Gogliotti et al (2016Gogliotti et al ( , 2017 and Supplemental Table 1]. As a baseline characterization of these new samples, we quantified MeCP2, mGlu 5 , and mGlu 7 protein expression and observed it to be significantly reduced in a manner similar to what we previously reported in the motor cortex (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor Cortex and Cerebellum RNA Sequencing. We recently obtained six cerebellum samples from RTT patient autopsies to serve as a complement to our existing work in the motor cortex, as well as eight age, sex, and PMI matched controls [described further in Gogliotti et al (2016Gogliotti et al ( , 2017 and Supplemental Table 1]. As a baseline characterization of these new samples, we quantified MeCP2, mGlu 5 , and mGlu 7 protein expression and observed it to be significantly reduced in a manner similar to what we previously reported in the motor cortex (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we obtained a set of RTT samples from the motor cortex of RTT patients in sufficient quantity to conduct RNA and protein analysis. These samples were previously used to profile the translational relevance of the preclinical target genes GRM5 (mGlu 5 ) (Gogliotti et al, 2016) and GRM7 (mGlu 7 ) (Gogliotti et al, 2017). Building on these data sets, we next asked the question of whether novel genes or pathways could be identified using transcriptomics.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported preclinical efficacy of mGlu 7 potentiation in a RTT mouse model. 16 One limitation of our previous work was the use of a nonselective compound that potentiates the activity of all group III mGlu receptors. The phenotypes reported here overlap extensively with those reported in RTT models (reviewed in 61), providing further support for mGlu 7 as a bona fide therapeutic target for RTT.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, singlenucleotide polymorphisms have been associated with increased risk for ASD, ADHD and schizophrenia. [12][13][14][15] We recently reported that mGlu 7 protein expression was significantly reduced in autopsy samples from patients with Rett syndrome (RTT), 16 suggesting that altered mGlu 7 expression can be a feature of monogenetic disorders in which the causative gene is not GRM7. In a mouse model of RTT, we found that potentiation of mGlu 7 activity with an allosteric modulator improved disease phenotypes.…”
Section: Mglumentioning
confidence: 99%
See 1 more Smart Citation